Autophagy in Staphylococcus aureus Infection - Wang, Mengyao; Fan, Ziyao; Han, Hongbing (Frontiers in Cellular and Infection Microbiology, 2021)
Staphylococcus aureus is an invasive, facultative intracellular pathogen that can colonize niches in various host organisms, making it difficult for the host immune system to completely eliminate. Host autophagy is an intracellular clearance pathway involved in degrading S. aureus. Whereas the accessory gene regulatory system of S. aureus that controls virulence factors could resist the host immune defenses by evading and even utilizing autophagy. This article reviews the interaction between autophagy and S. aureus, providing insights on how to use these mechanisms to improve S. aureus infection control.